A study on the evaluation of ice loads and pressure distribution using Pressure Indicating Film in ice-structure interaction. (1st October 2018) - Kim, Hyunwook; Daley, Claude; Colbourne, Bruce
Abstract: Many efforts have been made to investigate ice loads and pressure distributions occurring during ice-structure interaction in laboratory-scale tests. Based on results obtained utilizing a high-resolution 'Pressure Indicating Film (PIF)' during an ice crushing test, actual contact areas and spatial pressure distributions at each test step were re-examined according to the pixel resolutions. Furthermore, the resultant pressure distribution plot was utilized to estimate the maximum load to further evaluate the expanded utilization of the PIF by comparing the maximum load results measured by a load cell. The measurement of contact area during an ice-structure interaction using the PIF was found to be reasonably accurate. In the case of ice loads, the load values predicted by the PIF slightly overestimated the values to the load cell measurement. Highlights: High-resolution 'Pressure Indicating Film (PIF)' utilized during an ice crushing test. Maximum ice load results between PIF and load cell measurement were compared. Contact area measurement using the PIF was found to be reasonably accurate. The ice load measurement by the PIF generally overestimated the value. Crushing speed showed a noticeable effect on measured load variation.